PENINGKATKAN EKONOMI KERAKYATAN MELALUI PENGUATAN MANAGERIAL KOPERASI WANITA DI KECAMATAN PADEMAWU KABUPATEN PAMEKASAN - Rudy Haryanto (Research Institute and Community Engagement of IAIN MADURA, 2016)
This research is study of the economic empowerment of families and communities, especially women through strengthening women's cooperative management. This type of research used in this study is Participatory Action Research (PAR) with the object of research in True Women's Cooperative in the village of East Pademawu and Cooperative woman Tunas Jaya Village Bunder, District Pademawu Pamekasan. The data used are primary and secondary data were analyzed by the seven phases of activity, with qualitative and quantitative outputs and output target True empowerment of women cooperatives and Tunas Jaya for populist economic empowerment in rural East Pademawu and Bunder Pademawu District of Pamekasan.The results of the study justify that straight women's cooperatives located in the village of East Pademawu Pademawu District of Pamekasan. True women's cooperatives established on December 29, 2010 by the Law Firm 41 / BH / XVI.199 / 2010, and already have a TIN on behalf Kopererasi True Women. Cooperative Board Chairman Mrs. Suhemah straight woman, Mrs. Afiah Quetfiati Secretary, Treasurer and Trustees Mother Mother Kustina Suliha. Currently Cooperative straight women have received the grant twice Rp 50 million to Rp 875,000 principal savings and mandatory savings of Rp 10.165 million. So the woman straight Cooperative has a total capital of US 61.04 million of the 93 members. Meanwhile, women's cooperatives profile Tunas Jaya subdistrict located in the Village Bunder Pademawu Pamekasan. Women's cooperatives Tunas Jaya was established on December 29, 2010 by the Law Firm 180.1 / BH / XVI.199 / 2011, and already have a TIN on behalf Kopereraaaasi Women Tunas Jaya. Tunas Jaya Cooperative Management lady Mrs. Suniyah Chairman, Mrs. Nanik Hidayati Secretary, Treasurer Mrs. Indra Ningsih and Supervisory Capital Iswanyanti. Currently Tunas Jaya Cooperative woman has received one grant funds amounting to Rp 25 million to Rp 120,000 principal savings and mandatory savings of Rp 42,000. Tunas Jaya Cooperative so that women have a total capital of US 25.162 million of the 23 members. True women's cooperatives and shoots Jata pick the potential of the region and members that allows it to be further developed. And the support of both the government and the Provincial Government of the District Rural.